Timing of Visual Bodily Behavior in Repair Sequences: Evidence From Three Languages. Issue 3 (2nd April 2016) - Floyd, Simeon; Manrique, Elizabeth; Rossi, Giovanni; Torreira, Francisco
Abstract : This article expands the study of other-initiated repair in conversation—when one party signals a problem with producing or perceiving another's turn at talk—into the domain of visual bodily behavior. It presents one primary cross-linguistic finding about the timing of visual bodily behavior in repair sequences: if the party who initiates repair accompanies their turn with a "hold"—when relatively dynamic movements are temporarily and meaningfully held static—this position will not be disengaged until the problem is resolved and the sequence closed. We base this finding on qualitative and quantitative analysis of corpora of conversational interaction from three unrelated languages representing two different modalities: Northern Italian, the Cha'palaa language of Ecuador, and Argentine Sign Language. The cross-linguistic similarities uncovered by this comparison suggest that visual bodily practices have been semiotized for similar interactive functions across different languages and modalities due to common pressures in face-to-face interaction.